KEMAMPUAN MENULIS KARANGAN NARASI BAHASA MAKASSAR MENGGUNAKAN MEDIA VIDEO PEMBELAJARAN SISWA KELAS VIII SMP NEGERI 2 MAPPAKASUNGGU KABUPATEN TAKALAR - Juliana, Ela; Andi Agussalim AJ; Asri, Aswati (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This research aims to describe the ability to write narrative essays in Makassar language using learning video media for class VIII students at SMP Negeri 2 Mappakasunggu, Takalar Regency. This type of research is a type of quantitative research. The population of this study were all students in class VIII of SMP Negeri 2 Mappakasunggu, Takalar Regency, totaling 141 students. Determining the sample in this research used Krejcie Morgan's theory with a sample of 103 students. Data collection in this research was carried out using test techniques on research samples. All the data obtained was analyzed through several stages: 1) making a list of raw scores, 2) making frequency distributions and raw scores, 3) calculating the scores obtained by students, 4) calculating the average value of students, 5) classifying students' skills based on the references provided determined. The results of this research show that class VIII students of SMP Negeri 2 Mappakasunggu, Takalar Regency are categorized as capable in learning to write narrative essays in Makassar language using learning video media as seen from the grades and percentage of students who got a score of 75-100, namely 79 people (77%) from 103 samples and has reached the specified criteria, namely 75% of the sample getting 75 and above is categorized as capable.